THE IMPORTANCE OF PHYSICAL ACTIVITY FOR THE HEALTHY GROWTH AND DEVELOPMENT OF PRIMARY SCHOOL STUDENTS - Atabaeva D. T. (Galaxy International Interdisciplinary Research Journal, 2022)
This article is written about the importance of physical activity for healthy growth and development of Primary School students, for a strong immune system, and its components are information about the positive effect of morning physical education, sports, playing various games on the children's body.